2020
DOI: 10.1002/mds.28175
|View full text |Cite
|
Sign up to set email alerts
|

Elevated In Vitro Kinase Activity in Peripheral Blood Mononuclear Cells of Leucine‐Rich Repeat Kinase 2 G2019S Carriers: A Novel Enzyme‐Linked Immunosorbent Assay–Based Method

Abstract: The cross-sectional and longitudinal relationships between white matter hyperintensities and dementia in patients with Parkinson's disease: a retrospective analysis of 132 patients in a single center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 17 publications
4
29
0
Order By: Relevance
“…LRRK2 S935 phosphorylation rates decrease in LRRK2 carriers with PD, while all other groups show no significant differences in levels of the tested analytes (Padmanabhan et al, 2020). In another study, however, pS935-LRRK2 levels were reported to be slightly elevated in iPD patients (Melachroinou et al, 2020). To be fair, for this purpose, one must consider the most relevant cell type in which to measure LRRK2 markers.…”
Section: Measurement Of Lrrk2 In Blood and Blood Derivativesmentioning
confidence: 96%
See 3 more Smart Citations
“…LRRK2 S935 phosphorylation rates decrease in LRRK2 carriers with PD, while all other groups show no significant differences in levels of the tested analytes (Padmanabhan et al, 2020). In another study, however, pS935-LRRK2 levels were reported to be slightly elevated in iPD patients (Melachroinou et al, 2020). To be fair, for this purpose, one must consider the most relevant cell type in which to measure LRRK2 markers.…”
Section: Measurement Of Lrrk2 In Blood and Blood Derivativesmentioning
confidence: 96%
“…Secondly, "cellular" assays (measuring phosphorylation of LRRK2 or its substrates) provide a "snap-shot" of kinase activation that is the result of the coordinated action of myriad upstream and downstream regulatory factors, interacting proteins, and the general activation state of the cell. We have employed such an assay, initially in over-expression models (e.g., Leandrou et al, 2019), but more recently in a clinical study assessing LRRK2 in peripheral blood cells (Melachroinou et al, 2020). In this approach, LRRK2 is purified in an ELISA plate, capturing the protein with anti-LRRK2 (or epitope tag) antibodies, followed by an in-well kinase reaction in which the reaction mixture containing the peptide substrate is added directly to the well containing immobilized LRRK2.…”
Section: Intrinsic Lrrk2 Kinase Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The first cohort was recruited at Columbia University Irving Medical Center (hereinafter referred to as 'Columbia cohort' and color-coded with orange) [11,37]. Participants in the Columbia cohort included 35 HC, 16 NMC, 40 iPD, 28 LRRK2 PD individuals, and one PD patient with an unknown LRRK2 status.…”
Section: Overview Of Pd Cohorts For Urinary Proteomicsmentioning
confidence: 99%